Hydrazine mediated low temperature soft chemical synthesis of mixed metal oxide (γ-Fe2O3–ZnO) graphene nanocomposite: in vitro cytotoxicity study on HeLa and SK-BR-3 cell lines. (8th May 2019) - Naskar, Atanu; Jana, Batakrishna; Kim, Hong Gun; Kwac, Lee Ku
Abstract: Present work reports the successful synthesis of maghemite ( γ -Fe2 O3 )-zinc oxide (ZnO)-reduced graphene oxide (rGO) nanocomposite (IZG) adopting low temperature solution process. Zinc nitrate, iron nitrate and graphene oxide were used in the precursor medium. The IZG nanocomposite was synthesized by two-step low temperature solution process in presence of hydrazine hydrate. The existence and uniform distribution of γ -Fe2 O3, ZnO nanoparticles (NPs), in rGO nanosheets can be confirmed by x-ray diffraction and transmission electron microscopic studies of the samples. Other characterization techniques like Raman and x-ray photoelectron spectroscopic analyses were used to confirm the presence of chemical interaction/complexation between the available oxygen functionalities of rGO with the inorganic moieties of IZG sample. The in vitro cytotoxicity and quantitative cell viability of all the samples (upto a maximum of 200 μ g ml −1 ) on HeLa and SK-BR-3 cell lines was also studied. Among the samples, IZG sample showed an excellent biocompatibility than the other samples. This simple synthesis strategy could be applied for other mixed oxide nanocomposite synthesis and their biomedical applications.